2014
DOI: 10.1002/mus.24091
|View full text |Cite
|
Sign up to set email alerts
|

The effects of strength, aerobic, and concurrent exercise on skeletal muscle damage in rats

Abstract: Forty-eight hours was sufficient for complete recovery from oxidative stress and muscle damage in the SE and CE groups, but not in the AE group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…However, in highly trained athletes the balance between ROS/RNS and the intracellular antioxidant defences is tenuous. Athletes may not achieve the same benefits from RE training as more strenuous exercise sessions promote chronic oxidative stress (Tanskanen et al 2010), inflammation, muscle fatigue, pain (Kreher et al 2012) and damage (Turner et al 2011;Rech et al 2014). Therefore in this study we submitted rats to a high-intensity resistance exercise protocol, in conjunction with oral supplementation using L-glutamine and Lalanine, in either their free or DIP form, and investigated the GLN-GSH axis and HSP-27 mediated cytoprotection.…”
Section: R a F Tmentioning
confidence: 99%
“…However, in highly trained athletes the balance between ROS/RNS and the intracellular antioxidant defences is tenuous. Athletes may not achieve the same benefits from RE training as more strenuous exercise sessions promote chronic oxidative stress (Tanskanen et al 2010), inflammation, muscle fatigue, pain (Kreher et al 2012) and damage (Turner et al 2011;Rech et al 2014). Therefore in this study we submitted rats to a high-intensity resistance exercise protocol, in conjunction with oral supplementation using L-glutamine and Lalanine, in either their free or DIP form, and investigated the GLN-GSH axis and HSP-27 mediated cytoprotection.…”
Section: R a F Tmentioning
confidence: 99%
“…In animal model, focal edema and inflammation fibers were observed several days after eccentric exercise (Sudo and Kano 2009). The EI is also increased several days after exercise in animal (Rech et al 2014) and human (Chen et al 2012;Chen et al 2010). A previous study (Fujikake et al 2009) using rat tibialis anterior muscles observed EI change after injection of bupivacaine hydrochloride (BPVC) that induced muscle damage.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that enhanced muscle echo intensity (EI) obtained by ultrasonography was concomitant with increased muscle size (Chen and Nosaka 2006;Gonzalez-Izal et al 2014). The increase of EI is considered as an index of muscle tissue abnormality, muscle swelling, or muscle damage after the exercise (Fujikake et al 2009;Rech et al 2014). It is well known that eccentric contraction induces the delayed increase of EI at 2-5 days after exercise (Chen et al 2012;Chen et al 2010;Matta et al 2018), but the acute change of EI inconsistent in previous literature (Jenkins et al 2015;Muddle et al 2019;Radaelli et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, using malondialdehyde (MDA), Araneda et al (2014) observed no evidence of lipid peroxidation, when measured 80 min after a 10-km run. The marker used not only to characterise oxidative stress, but also the time of measurement postexercise as well as to crucial variables (Michailidis et al, 2007;Rech et al, 2014). Indeed, it has been observed that the levels of biomarkers of lipid peroxidation may be maximal immediately after exercise or until 1 hour after the end of exercise in blood (Michailidis et al, 2007;Samitas et al, 2009).…”
Section: Discussionmentioning
confidence: 99%